RESPON KONSUMEN TERHADAP WIRE JEWELRY PADA BROS DENGAN BAHAN KAWAT ALUMINIUM - Setyorini, Ayu Aris (Universitas Negeri Surabaya, 2020)
Brooch wire jewelry is one of the handicraft to jewelry to attract consumer response. The purpose of this study is to understand the consumer response of brooch wire jewelry in terms of color, shape, and size. The type of this study is the preference test using hedonic test. The data was collected by using e-questionnaire of google form were collected on sosial media a much 125 people and sample collected that 100 peopel. Analyzed data which used to measure consumer response of brooch wire jewelry by using its mean score. The result of this study show consumer response of brooch wire jewelry with highest mean for color aspect F design with a mean of 4.24, shape aspect F design with the mean 4.24 and size aspect F design 4.19. Keywords : Brooch, Consumer Response, Wire Jewelry.